ANALISIS TINGKAT KERAWANAN BAHAYA SAMBARAN PETIR DENGAN METODE SIMPLE ADDITIVE WEIGHTING DI PROVINSI BALI - Gunawan, Tomy; Suarbawa, Komang Ngurah; Pandiangan, Lestari Naomi L. (BULETIN FISIKA; Vol 15 No 2 (2014): BULETIN FISIKA)
Bali is a potential area prone to lightning strikes because it has a tropical climate with the possibility of rain accompanied by lightning quite high and also vulnerable because of the population density is very high. These conditions threaten the safety of lives and property of the population, so it is necessary to study the vulnerability of lightning strikes in Bali. For identify the level of vulnerability to lightning strikes used two factors, the threat factors using CG(Cloud to Ground) lightning incidence data (2009-2013) and vulnerability factors using data of population density and land use for homes and buildings. Two factors were analyzed using the method of SAW (Simple Additive Weighting) to obtain level of vulnerability to lightning strikes each district. The results of the calculations show Selemadeg Barat, Denpasar, Kuta, Pupuan, Klungkung and Selemadeg have a high level of vulnerability to lightning strikes, 27 districts are in the middle category and the remaining 21 districts are in the low category.